(untitled) (Journal of Asian Development Studies, 2013)
This research paper is an attempt to provide a national picture of commercial sexual exploitation of women and children in Pakistan. The study documents the magnitude, incidence and consequences of various types of violence against women and children engaged in beggary and sex business. For each type of violence against women and children addressed, the study also reviews what is known about the causes and associated risk and protective factors. Its focus is on prevention strategies, in particular through the identification of best practices in prevention, including those designed by the victims themselves. It surveys legal responses to violence and services for women children who have been its victims, again including interventions devised by women and children; furthermore, the study describes the evidence demonstrating which interventions work, which are promising, and which have been shown to be ineffective. The study provokes comprehensive national reviews of the situation of violence against women and children as possible covering, among other things, prevalence, legal frameworks, child protection systems, statistics, violence in institutions, evaluation of reports and recording of data and initiatives to protect children and prevent violence against them that have proven to be effective. The process of the preparation of the study includes consultations at the local and national levels which aim to ensure that all parts of civil society pay increased attention to violence against women and children. The study seeks to generate sharing approaches to the issue, in particular from a South and South Asia perspective. Efforts are made to discern gaps in legal protection at the local and national levels and to put forward specific proposals for strengthening legal standards, policies and programs.